The Moderating Role of Green Accounting on Sustainability Reporting in Indonesian Manufacturing - Hidayat, Imam; Petty Aprilia Sari; Sazali Zainal Abidin (Riset Akuntansi dan Keuangan Indonesia, 2026)
This study seeks to examine the impact of stakeholder pressure, corporate governance, and digital innovation on sustainability reporting, with green accounting acting as a moderating variable in manufacturing firms listed on the Indonesia Stock Exchange. The research covers a three-year period from 2022 to 2024, with the study population consisting of all manufacturing companies listed during that time. Using purposive sampling, 41 companies met the criteria and were selected as the sample. The study relies on secondary data sourced from the Indonesia Stock Exchange website, and the analysis was conducted using Moderated Regression Analysis. The findings indicate that creditor pressure, shareholder pressure, audit committees, independent commissioners, boards of directors, and digital innovation collectively affect sustainability reporting, while green accounting is capable of moderating the relationship between these independent variables and sustainability reporting. On a partial basis, creditor pressure, shareholder pressure, and the board of directors demonstrate a positive and significant effect on sustainability reporting, whereas audit committees, independent commissioners, and digital innovation show no effect. Moreover, green accounting is found to moderate the role of independent commissioners on sustainability reporting, but it does not moderate the effects of creditor pressure, shareholder pressure, audit committees, boards of directors, or digital innovation.